Statistical analysis plan for the ‘Tranexamic acid for hyperacute primary IntraCerebral Haemorrhage’ (TICH-2) trial - Flaherty, Katie; Bath, Philip M.W.; Dineen, Robert; Law, Zhe; Scutt, Polly; Pocock, Stuart; Sprigg, Nikola (BioMed Central, 2017)
Rationale